Integration of Local Culture and Ijen Geopark in Early Childhood Education Student Learning in Banyuwangi: Integrasi Budaya Lokal dan Geopark Ijen dalam Pembelajaran Siswa PAUD di Banyuwangi - Riztika Widyasari; mahfud; Triana Kartika Santi; Andhika Wahyudiono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Early childhood education in Banyuwangi faces challenges in the integration of local culture and the potential of the Ijen Geopark. Around 40% of PAUD institutions implement a curriculum based on local culture. The limited understanding of educators and the lack of exploration activities hinder the use of Geoparks as a learning medium. The lack of community support and facilities in PAUD exacerbates this situation. The purpose of this research is to integrate local culture and the natural potential of the Ijen Geopark in early childhood education in Banyuwangi. This study assesses the challenges and opportunities for the implementation of cultural and environment-based learning. The research methodology uses a qualitative approach based on literature review. This study collected data from journals and relevant documents. The main focus of the research is the challenge in the application of culture-based learning in early childhood education. The results of the study show the importance of integrating contextual learning that links culture and environment in early childhood education in Banyuwangi. The Ijen Geopark offers great potential to enrich children's learning experience through direct interaction with nature and local culture. By utilizing a context-based learning approach, children can understand the environmental and cultural values that exist around them. An effective learning process requires a connection between new knowledge and the social context that the child recognizes, so that the learning experience gained becomes more profound and meaningful. The conclusion of the study shows that Early Childhood education in Banyuwangi faces challenges in the low implementation of the local culture-based curriculum, understanding of the Ijen Geopark, and limited facilities. Training, infrastructure upgrades, and collaboration are required for solutions.